RISK FACTORS OF HYPERTENSION IN THE ELDERLY - Debie Anggraini (Yayasan Nusantara Hasana Berdikari, 2024)
Hypertension is caused by an abnormal increase in blood pressure beyond normal values, namely systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg measured at least twice in a sitting position. Hypertension indicates the occurrence of hemodynamic imbalance in the cardiovascular system caused by several aspects or multi-aspects and difficult to detect with one aspect only Methods: Hypertension detected during a physical examination is caused by certain diseases, so it is referred to as